Implementasi Data Warehouse Dan Penerapannya Pada PHI-Minimart Dengan Menggunakan Tools Pentaho dan Power BI - udayana, gede acintia; Mahendra, I Made Yoga; Sukawirasa, I Kadek Anom; Dimastawan Saputra, Gde Deva; Mahendra, Ida Bagus Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 10 No 1 (2021): JELIKU Volume 10 No 1, Agustus 2021DO - 10.24843/JLK.2021.v10.i01.p19, 2021)
A shop owner needs an information system to see sales conditions. However, PHI Minimart only provides sales information that is stored in a database so that it cannot provide or present information quickly. To solve this problem, a data warehouse was built at PHI Mart to get fast information. This research will carry out the implementation of data warehouse sales from data sources, the extraction, transformation, loading (ETL) process using Pentaho tools, making Starschema in the form of branch dimensions, product dimensions, employee dimensions, time dimensions connected to the sales fact table, dashboard using BI power. Then the results of the data warehouse are analyzed through the OLAP (On-line Analytical Processing) process, making a cube or schema workbench, and making a dashboard for visualization in presenting the expected information from PHI Minimart. The results in this study include sales data used in 2008 in the form of sales graphs or dashboards, goods sold, and total sales of each branch, which are obtained as the delivery of sales information at the store.